2011
DOI: 10.1124/dmd.111.039115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Renal Failure on Kidney Drug Transporters and Cytochrome P450 in Rats

Abstract: ABSTRACT:Chronic renal failure (CRF) leads to decreased drug renal clearance due to a reduction in the glomerular filtration rate. However, little is known about how renal failure affects renal metabolism and elimination of drugs. Because both depend on the activity of uptake and efflux by renal transporters as well as enzymes in tubular cells, the purpose of this study was to investigate the effects of CRF on the expression and activity of select renal drug transporters and cytochrome P450. Two groups of rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 38 publications
2
91
1
Order By: Relevance
“…Our studies focus largely on the effects of uremic toxins on influx transporters in the kidney; however, studies are clearly needed to understand the effects of uremic solutes on renal efflux transporters as well. Although there are studies showing interaction between uremic solutes and efflux transporters, 75 61,78,79 while renal P-gp showed no change. 79 Effect of uremic solutes on regulating renal transporter expression is still unclear.…”
Section: Clinical Evidence Supporting the Role Of Uremic Solutes In Mmentioning
confidence: 93%
“…Our studies focus largely on the effects of uremic toxins on influx transporters in the kidney; however, studies are clearly needed to understand the effects of uremic solutes on renal efflux transporters as well. Although there are studies showing interaction between uremic solutes and efflux transporters, 75 61,78,79 while renal P-gp showed no change. 79 Effect of uremic solutes on regulating renal transporter expression is still unclear.…”
Section: Clinical Evidence Supporting the Role Of Uremic Solutes In Mmentioning
confidence: 93%
“…For example, in rat (r) models of chronic renal failure the total protein expression levels of rOat1, rOat2, rOat3, and rUrat1 were reduced significantly. 25,26 Similarly, decreased human (h)OAT1, or rOat1 and rOat3, protein expression was observed in acute renal failure patients or animals with experimentally induced acute renal failure. [27][28][29][30] Renal proximal tubule cell loss owing to injury is likely a major contributing factor to this decrease in total protein expression level.…”
Section: Oats As Determinants In Tubular Secretion Of Uremic Toxinsmentioning
confidence: 99%
“…121 Furthermore, protein expression of CYP1A decreased in proximal tubule (ie, human kidney (HK)-2) cells treated with serum from CRF rats, whereas CYP3A expression was unaffected. 122 With regard to phase II metabolism, it has been shown that the pharmacokinetics of multiple drugs that are completely dependent on phase II enzymes for their clearance are changed in patients with CKD. For instance, acetylation of isoniazid is decreased as well as the glucuronidation of morphine, p-aminobenzoic acid, and metoclopramide.…”
Section: Intracellular Fate Of Uremic Toxinsmentioning
confidence: 99%
“…However, several studies in rats [1][2][3][4][5][6] and in patients [7] have shown that renal failure also decreases the metabolic clearance of drugs, particularly those metabolized by cytochrome P450 (CYP) and substrates of some drug transporters. The underlying causes of altered functional expression of CYPs and drug transporters observed in kidney disease remain unclear, but several studies indicate that uremic toxins may play a role via transcriptional or translational modifications of CYP and drug transporter enzymes [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%